LEGALITY APPLICATION FOR CHILDREN'S RIGHTS BY FAMILY PARTIES THROUGH THE RELIGIOUS COURT - Nasrullah Nasrullah (Universitas Islam Negeri (UIN) Mataram, 2020)
A child custody environment that is not conducive can hamper children's development because the child's rights are not fulfilled properly. In a family environment that is not conducive (broken home), the authority of child custody is often debated and even unclear. In addition to the disruption of the child's custody environment as a result of an unfavorable environment, it is not uncommon for parents of children to choose to transfer custody of their children to be cared for by parties other than the family, or even entrusted to orphanages. In the transfer of the environment of child custody to someone other than the family or to an orphanage, it is necessary to have the legality of the court as a legal basis for care that has various legal effects as a consequence of the transfer of the environment of child custody. On the one hand, the Religious Courts, which are one of the implementing agencies for judicial power in Indonesia, do not have a clear legality basis in examining, deciding, and resolving cases of custody applications filed by other than the family. So that the existence of the Religious Courts in examining, deciding, and resolving cases of a petition for child custody is important to be studied, because given the absence of regulations that clearly regulate the authority for the Religious Courts to hear cases of requests for child care or custody of children submitted by other than family party. This research is field research which is classified as qualitative research that combines theory and practice in the field which produces answers that do not number. The results showed that the religious court can examine, decide and settle cases of child custody applications filed by other than the family with reference to two general foundations, namely the juridical foundation and the philosophical basis.